2010
DOI: 10.1007/s10902-010-9208-8
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Happiness: The Importance of Social Capital

Abstract: Happiness, Social capital, Trust, Obligations, Information channel,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(96 citation statements)
references
References 29 publications
6
83
1
6
Order By: Relevance
“…As regards the other instrument, social trust has been found to be significantly and positively correlated with happiness in most individual-level studies on social capital and well-being (see, for example, Diener and Seligman 2004;Heliweel 2006;Bjørnskov 2008;Leung et al 2011;Requena 2010). The correlation has been confirmed also at the cross-country level (Bjørnskov 2006).…”
Section: Instrumental Variablesmentioning
confidence: 83%
“…As regards the other instrument, social trust has been found to be significantly and positively correlated with happiness in most individual-level studies on social capital and well-being (see, for example, Diener and Seligman 2004;Heliweel 2006;Bjørnskov 2008;Leung et al 2011;Requena 2010). The correlation has been confirmed also at the cross-country level (Bjørnskov 2006).…”
Section: Instrumental Variablesmentioning
confidence: 83%
“…A large strand of literature suggests that individual happiness is largely influenced by social capital such as trust, social interactions and civic traditions (Putnam 2000;Helliwell and Putnam 2004;Winkelmann 2009;Leung et al 2011;Helliwell and Barrington-Leigh 2011;Rodriguez-Pose and von Berlepsch 2011). Table 4 introduces the estimated empirical happiness model with social capital and trust covariates.…”
Section: Baseline Resultsmentioning
confidence: 99%
“…Furthermore, with the deepening of research, it is found that the emotion experience of community residents and the stock of social capital owned by residents have an important role in the residents' life satisfaction [20,21]. Therefore, a question arises as to whether there is a relationship between social capital, emotion experience and life satisfaction and whether the relationship between them to generate synergies and strengthen the effect of promoting community sustainable development.…”
Section: Introductionmentioning
confidence: 99%